The way people live - Branson, Margaret Stimmann (Boston : Houghton Mifflin, 1976)
Examines what distinguishes man from other animals, what makes men different, what causes and changes culture, and what happens to an urbanized earth.
Keywords: Anthropology; Social sciences; Anthropology -- Juvenile literature; Social sciences -- Textbooks; Anthropology; Social sciences